PENENTUAN PRIORITAS PERBAIKAN JALAN MENGGUNAKAN METODE BINA MARGA (STUDI KASUS : JALAN TAMAN BUAH, KOTA GORONTALO) - Madjowa, Nona fitriana; Abdul Muiz Mahmud; Ahmad Fathan If Hadju; Siskawati Madjid; Amanda Putri Halid (Universitas Bina Taruna Gorontalo, 2025)
The objective of this study is to assess the extent of road damage and determine the priority level for road maintenance using the 1990 Bina Marga Method on Taman Buah Street, located in Gorontalo City. This research employed a survey method to evaluate pavement damage along Taman Buah Street. The assessment was conducted based on the types of pavement distress in accordance with the 1990 Bina Marga Method. The study began with measurements to determine the length and width of the road. A visual inspection was then carried out to identify and measure the extent of damage. The survey data were recorded on standardized survey forms and analyzed to calculate the Road Condition Index using the Bina Marga method. Based on the analysis, the road condition value of Taman Buah Street is 6, with 50.15% of the total pavement area affected by damage. The types of damage identified include cracking (both alligator and longitudinal cracks), patches, potholes, surface hardness issues such as raveling, and settlements. According to the Bina Marga Method, the Priority Ranking Value for Taman Buah Street is 5, which categorizes the road into the Periodic Maintenance Program.